Razpad partnerske zveze na prehodu v odraslost - Zgaga, Simona (Psihološka obzorja (Ljubljana), 2012)
Relationship termination happens relatively often in emerging adulthood but is nevertheless as distressing then as it is later in life. We examined the relationship between coping strategies and posttraumatic growth in a sample of 260 emerging adults whose heterosexual romantic relationships were terminated at most two years before participating in the study. Participants completed The Posttraumatic Growth Inventory, The COPE Inventory and Emotion Approach Coping scale. For the purposes of the study we also conceptualized a new coping inventory, related specifically to coping with relationship termination. While controlling for gender and age the coping strategies explained 34 % of variability in posttraumatic growth. Statistically significant predictors of posttraumatic growth were problem-oriented coping strategies, coping strategies, oriented towards emotions and other people, acceptance and positive self-motivation as well as coping strategies that allow some distancing from the stressor. Results indicate that posttraumatic growth is related to problem-oriented and also to emotion-oriented coping strategies, which is reasonable since relationship termination is a stressor that cannot be eliminated. It is important that an individual who is facing it can cope well with the unpleasant emotions deriving from relationship termination.
Keywords: parnerska zveza; ločitev; posttravmatska rast; stres; odraslost; Vprašalnik posttravmatske rasti (PTGI); Vprašalnik spoprijemanja (COPE); Vprašalnik na čustva usmerjenega spoprijemanja (EAC); Vprašalnik spoprijemanja s stresom po razpadu partnerske zveze